Conversion of the sensor kinase DcuS of Escherichia coli of the DcuB/DcuS sensor complex to the C4‐dicarboxylate responsive form by the transporter DcuB. (12th July 2016) - Wörner, Sebastian; Strecker, Alexander; Monzel, Christian; Zeltner, Matthias; Witan, Julian; Ebert‐Jung, Andrea; Unden, Gottfried
Summary: The sensor kinase DcuS of Escherichia coli co‐operates under aerobic conditions with the C4 ‐dicarboxylate transporter DctA to form the DctA/DcuS sensor complex. Under anaerobic conditions C4 ‐dicarboxylate transport in fumarate respiration is catalyzed by C4 ‐dicarboxylate/fumarate antiporter DcuB. (i) DcuB interacted with DcuS as demonstrated by a bacterial two‐hybrid system (BACTH) and by co‐chromatography of the solubilized membrane‐proteins (mHPINE assay). (ii) In the DcuB/DcuS complex only DcuS served as the sensor since mutations in the substrate site of DcuS changed substrate specificity of sensing, and substrates maleate or 3‐nitropropionate induced DcuS response without affecting the fumarate site of DcuB. (iii) The half‐maximal concentration for induction of DcuS by fumarate (1 to 2 mM) and the corresponding Km for transport (50 µM) differ by a factor of 20 to 40. Therefore, the fumarate sites are different in transport and sensing. (iv) Increasing levels of DcuB converted DcuS from the permanent ON (DcuB deficient) state to the fumarate responsive form. Overall, the data show that DcuS and DcuB form a DcuB/DcuS complex representing the C4 ‐dicarboxylate responsive form, and that the sensory site of the complex is located in DcuS whereas DcuB is required for converting DcuS to the sensory competent state.